Analisis Pengaruh Data Curah Hujan terhadap Desain Saluran Kota - Kerlima Hutagaol; Akhmad Faruq; Maret Jerman Samosir; Nanang Andhy Setiawan; Meliana Nur Evani; Pandya Fadil Munpintoro (Pusat riset dan Inovasi Nasional, 2025)
Currently, the world is facing Global Warning Phenomena, El Nino and La Nina, each of these natural phenomena makes above-average rainfall at a time and place and an area, especially impacting large cities that are passed through by water due to high rainfall. With inadequate city channels to accommodate rainwater flow, it results in, among other things, high floods, landslides due to the soil no longer being able to accommodate high rainfall, high Rob floods due to seawater overflowing into coastal areas of the city. Based on the disaster data due to high rainfall, Research, Handling and Mitigation Planning is needed with the aim of obtaining data for drainage design. The study is the observation of rainfall for 2 years, 5 years, 10 years, and 20 years, so that by calculating the intensity of rain using the Gumbel and Pearson III Log distribution methods, accurate data is obtained to determine the drainage dimensions that must be made in a city and the dimensions of retaining walls along the coast to overcome storm disasters in coastal areas or big cities.